PENGEMBANGAN AGROWISATA DESA BUAHAN KAJA MELALUI IDENTIFIKASI POTENSI, PENGEMASAN PAKET WISATA, DAN PELATIHAN SUMBERDAYA MANUSIA - Rai, I.N.; Sudana, I.P.; Semarajaya, C.G.A.; Wiraatmaja, I.W. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Buahan Kaja village which located at district of Payangan, Gianyar Regency has a unique nature and culture and a wide range of agriculture activities. Those are very potential to be developed into agro-tourism and in turn increasing income and welfare of the community. The objective of the community service was to develop agro-tourism in Buahan Kaja village through identification of agro-tourism village’s potency, packaging tour and tracking activities, and training of human resources. Problems in developing of agro-tourism at Buahan KajaVillage were less participation of the community and lack of human resources that capable in this concern including all agro-tourism activities such as packaging tour activities, tourist guiding, brochure preparation, agro-processing, and marketing of agro-tourism package. The current community service has been successfully solved the problem by providing a complete guide books of agro-tourism at Buahan Kaja village. Through training which have been conducted, the community service also increased knowledge and skills of the community in managing of agro-tourism.